A Property Tax Cap for Maine? Roots of Voter Discontent and Likely Impacts - LaPlante, Josephne (Maine Policy Review, 1996)
In Maine, as in many other states, there is evidence of a growing sentiment to cap the property tax. Josephine LaPlante tackles this issue head on. Following a brief review of property tax limitation efforts in Maine and elsewhere, she provides an analysis of the impacts a property tax cap would have on the state.